MIND, SELF, AND SOCIETY IN THE ONLINE GAY COMMUNITY: Study on Grindr Apps - Pranata, Rendy Harsono; Putri, Dianingtyas M. (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2020)
Self-identity is a unified thing with someone's self-concept. The experience that is owned by someone is personal knowledge from experiencing and having various moments and references. The advancement of information technology in the Industry 4.0 era is now facing 5.0, opening up the opportunity to youths especially generation Z (Gen Z) who much more cares about freedom, having high self-confidence, and capability to quickly adopt various applications across internet media outlets. Nevertheless, they lack eagerness to dig deeper into something. Those factors have influenced the development of their self-concept through internet media. Grindr has known as an online gay-dating application, where a homosexual male exposes himself to what he wants to be seen by other users. This article focused on the review and describe how the self-concept development process of gen Z in using the application. Analyze the research using Mead's symbolic interactionism theory, furthermore to find out what factors that influence self-concept development of the application active users in their daily life. This research using virtual ethnography to four homosexual men in the age of 16-23. The results indicated that through the online application, a homosexual male is capable to develop his self-concept that wants to be seen on that medium. Moreover, the close read of data also uncovered at least ten types of aforesaid application users based on the self-concept that they formÂ To cite this article (7th APA style): Pranata, R. H. and Putri, D. M. (2020). Mind, Self, and Society in the Online Gay Community: Study on Grindr Apps. Journal Communication Spectrum: Capturing New Perspectives in Communication, 10(1), 68-82. http://dx.doi.org/10.36782/jcs.v10i1.2007